Photojournalism and proximity images: two points of view, two professions? - Thierry, Daniel (Brazilian journalism research, 2011)
For many decades, classic photojournalistic practice, firmly anchored in a creed established since Lewis Hine (1874-1940), has developed a praxis and a doxa that have barely been affected by the transformations in the various types of journalism. From the search for the “right image” which would be totally transparent by striving to refute its enunciative features from a perspective of maximumobjectivity, to the most seductive photography at supermarkets by photo agencies, the range of images seems to be decidedly framed. However, far from constituting high-powered reportingor excellent photography that is rewarded with numerous international prizes and invitations to the media-artistic world, local press photography remains in the shadows. How does oneoffer a representation of one’s self that can be shared in the local sphere? That is the first question which editors of the local daily and weekly press must grapple with. Using illustrations of the practices, this article proposes an examination of the origins ofthese practices and an analysis grounded on the originality of theauthors of these proximity photographs.